Egaliter Masa Majapahit: Studi Kasus Penguasa Perempuan Majapahit Tribhuwanottuṅgadewī Jayawiṣṇuwarddhanī, 1329-1350 - Mu'aafi, Gilang Harits; Yuliati, Yuliati; Khakim, Moch. Nurfahrul Lukmanul (Universitas Hamzanwadi, 2022)
In ancient Java, women and men had an equal position in politics. This equality can be seen from the mention of men and women who have positions in high positions in royal politics. These positions include crown son/princess, regional ruler to the supreme ruler as the king/empress of the kingdom. This research uses historiographic methods that go through five stages, including topic selection, heuristics, source verification, source interpretation and historiography. This research found that during the Majapahit period, in addition to women having an equal position, women during the Majapahit era had also received legal protection as stated in Kutaramanawa. In addition to obtaining legal protection, women during the Majapahit period also had the same opportunity to obtain education or political training. Tribhuwanottuṅgadewī and Rājadewī had been given the opportunity to occupy the territories of vassal kingdoms as regional rulers in Kahuripan and Daha. After Tribhuwanottuṅgadewī ascended the throne to become empress in 1329, Gayatrī guided and played a behind the scenes role in the reign of Tribhuwanottuṅgadewī. During the Majapahit era, women had an important position in royal politics, ranging from rulers (central and regional) to playing a role behind the scenes of government.Pada masa Jawa Kuno perempuan dan laki-laki mempunyai kedudukan yang setara dalam bidang politik. Kesetaraan tersebut terlihat dari disebutkannya laki-laki dan perempuan yang mempunyai kedudukan dalam jabatan tinggi politik kerajaan. Jabatan tersebut antara lain putra/putri mahkota, penguasa daerah hingga penguasa tertinggi kerajaan. Penelitian ini menggunakan metode historiografi yang melalui lima tahapan, diantaranya pemilihan topik, heuristik, verifikasi sumber, interpretasi sumber dan historiography. Penelitian ini menemukan bahwa pada masa Majapahit selain perempuan telah mempunyai kedudukan yang setara, perempuan pada masa Majapahit juga telah memperoleh perlindungan hukum seperti yang telah tertera dalam Kutaramanawa. Selain memperoleh perlindungan hukum, perempuan pada masa Majapahit juga telah mempunyai kesempatan yang sama untuk memperoleh pendidikan ataupun pelatihan politik. Tribhuwanottuṅgadewī dan Rājadewī telah diberikan kesempatan untuk menduduki wilayah kerajaan bawahan sebagai penguasa daerah di Kahuripan dan Daha. Setelah Tribhuwanottuṅgadewī naik tahta menjadi ratu tahun 1329, Gayatrī membimbing serta berperan dari balik layar pemerintahan selama pemerintahan Tribhuwanottuṅgadewī. Pada masa Majapahit perempuan telah mempunyai kedudukan penting dalam politik kerajaan, mulai dari penguasa (pusat dan daerah) hingga berperan dari balik layar pemerintahan.